Role of trust in sustaining provision and uptake of maternal and child healthcare: Evidence from a national programme in Nigeria. (January 2022) - Ezumah, Nkoli; Manzano, Ana; Ezenwaka, Uchenna; Obi, Uche; Ensor, Tim; Etiaba, Enyi; Onwujekwe, Obinna; Ebenso, Bassey; Uzochukwu, Benjamin; Huss, Reinhard; Mirzoev, Tolib
Abstract: Despite increasing attention to implementation research in global health, evidence from low- and middle-income countries (LMICs) using realist evaluations, in understanding how complex health programmes work remains limited. This paper contributes to bridging this knowledge gap by reporting how, why and in what circumstances, the implementation and subsequent termination of a maternal and child health programme affected the trust of service users and healthcare providers in Nigeria. Key documents were reviewed, and initial programme theories of how context triggers mechanisms to produce intended and unintended outcomes were developed. These were tested, consolidated and refined through iterative cycles of data collection and analysis. Testing and validation of the trust theory utilized eight in-depth interviews with health workers, four focus group discussions with service users and a household survey of 713 pregnant women and analysed retroductively. The conceptual framework adopted Hurley's perspective on 'decision to trust' and Straten et al.'s framework on public trust and social capital theory. Incentives offered by the programme triggered confidence and satisfaction among service users, contributing to their trust in healthcare providers, increased service uptake, motivated healthcare providers to have a positive attitude to work, and facilitated their trust in the health system. Termination of the programme led to most service users' dissatisfaction, and distrust reflected in the reduction in utilization of MCH services, increased staff workloads leading to their decreased performance although residual trust remained. Understanding the role of trust in a programme's short and long-term outcomes can help policymakers and other key actors in the planning and implementation of sustainable and effective health programmes. We call for more theory-driven approaches such as realist evaluation to advance understanding of the implementation of health programmes in LMICs. Highlights: Implementation research using realist evaluation helps explain health programmes. Financial incentives improve trust contributing to increased use of healthcare. Training, remuneration and facility upgrades improve health workers' motivation. Loss of incentives and remuneration reduces trust, but residual trust can remain. Theory-driven evaluations can explain and help improve complex health programmes.